Philosophical perspectives on teacher education - Heilbronn, Ruth; Foreman-Peck, Lorraine; Biesta, Gert. (Chichester, West Sussex, UK ; Malden, MA : Wiley Blackwell, 2015)
"Philosophical Perspectives on Teacher Education presents a series of well-argued, thought-provoking essays that point to the ethical considerations that should be addressed when proposing and implementing teacher training and educational policies and practices"--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Teachers -- Training of -- Philosophy; EDUCATION -- Philosophy & Social Aspects; Teachers -- Training of -- Philosophy; EDUCATION / Administration / General; EDUCATION / Organizations & Institutions; Electronic books